The levels of trace elements in sputum as biomarkers for idiopathic pulmonary fibrosis. (May 2021) - Forte, Giovanni; Bocca, Beatrice; Pisano, Andrea; Collu, Claudia; Farace, Cristiano; Sabalic, Angela; Senofonte, Marta; Fois, Alessandro Giuseppe; Mazzarello, Vittorio Lorenzo; Pirina, Pietro; Madeddu, Roberto
Abstract: Idiopathic pulmonary fibrosis (IPF) is a rare lung disease that quickly leads to death. This paper addressed the issue of whether the levels of trace elements in sputum samples are suitable biomarkers for IPF disease. The sputum Cd, Cr, Cu, Fe, Mn, Ni, Pb and Zn concentrations were measured by sector field inductively coupled plasma mass spectrometry in populations sampled in Sardinia Island (Italy) including 31 patients with IPF, 31 patients with other lung-related diseases and 30 age- and gender-matched healthy controls. Risk factors in the disease as gender, age, severity and duration of the disease were assessed. Results showed that IPF patients had significantly increased sputum levels of Cd, Cr, Cu and Pb respect to controls. In males, but not in females, sputum levels of Cd, Cr and Cu were significantly higher in IPF cases respect to controls. In addition, Cr and Pb were increased in male patients with IPF compared to male patients with other lung diseases. Regarding Zn, it was found higher with the more serious stage of disease. Moreover, the ratios Cu/Zn, Fe/Mn and Cu/Mn were significantly increased in IPF patients and in non-IPF patients than in control subjects. These data showed clear increases in the concentration of some trace elements in sputum from patients with IPF and patients with other lung-related diseases that may contribute to the injury. The non-invasiveness of the sputum analysis is beneficial for its use as biomarker of trace element status in diseased patients for both the researcher and the clinic. Highlights: Idiopathic pulmonary fibrosis (IPF) is a lung disease leading rapidly to death. IPF patients had significantly increased sputum levels of Cd, Cr, Cu and Pb respect to controls. In males, IPF patients showed significantly increased sputum levels Cr and Pb than patients with other lung diseases. Zn in sputum was found higher with the more serious stage of IPF disease. Measurement of trace element in sputum may become a non-invasive analysis for IPF and other lung diseases.